A LAZER STAR AS A REFERENCE RADIATION SOURCE IN FORMING NONDISTORTED AES IMAGES - Bacoot, P. A.; Ershova, O. M.; Shumilov, Yu. P.; Dobrovolsky, A. V. (Одеські астрономічні публікації, 2017)
In the work, a possibility is shown of using an artificial laser source (a laser star) as a reference one to obtain an undistorted image of artificial Earth's satellites.